Implementation of Full Adder Using 5-Input Majority Gate - Erniyazov, Sarvarbek; Cheol Jeon, Jun (International Journal of Engineering and Technology, 2018)
In this paper full adder was created employing five-input majority gate according to Quantum-Dot Cellular Automata (QCA) innovation. We used the QCA logic in our modified structure to reduce the delay. That report details the structure furthermore investigate associated with QCA dependent 1-bit full adder design for minimal energy purposes. This method permits decreasing energy expenditure, delay, additionally location involving electronic circuits.Â Â